2022
DOI: 10.1002/cam4.4942
|View full text |Cite
|
Sign up to set email alerts
|

Statins associate with lower risk of biliary tract cancers: A systematic review and meta‐analysis

Abstract: Background Biliary tract cancers (BTCs), encompassing cholangiocarcinoma (CCA), gallbladder (GBC), and ampulla of Vater cancers (AVC), are common hepatobiliary cancer after hepatocellular carcinoma with a high mortality rate. As there is no effective chemopreventive agent to prevent BTCs, this study aimed to explore the role of statins on the risk of BTCs. Methods PubMed, Embase, and Cochrane Library from inception until 24 April 2020 were searched according to the Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Liu et al reported that statin use was associated with a nearly 12% lower risk of bile duct cancer (OR = 0.88, 95% CI: 0.79-0.98), compared with non-use of statins. Meanwhile, the latest metaanalysis based on eight observational studies also supported this correlation (Cheung et al, 2023). Conversely, from the same European population, the team of Tran et al (Tran et al, 2020) yielded the benefits role of statin use in liver cancer prevention (OR = 0.48, 95% CI: 0.24-0.94) but not in bile duct cancer (HR = 1.09, 95% CI: 0.45-2.64).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Liu et al reported that statin use was associated with a nearly 12% lower risk of bile duct cancer (OR = 0.88, 95% CI: 0.79-0.98), compared with non-use of statins. Meanwhile, the latest metaanalysis based on eight observational studies also supported this correlation (Cheung et al, 2023). Conversely, from the same European population, the team of Tran et al (Tran et al, 2020) yielded the benefits role of statin use in liver cancer prevention (OR = 0.48, 95% CI: 0.24-0.94) but not in bile duct cancer (HR = 1.09, 95% CI: 0.45-2.64).…”
Section: Discussionmentioning
confidence: 94%
“…Statins, the inhibitors of 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase (HMGCR), are commonly used as lipid-lowering drugs for atherosclerosis ( Ziaeian and Fonarow, 2017 ). Recently, statins have also received increasing attention owing to the rate-limiting enzyme in the mevalonate pathway (a pathway controlling a range of cell signaling molecules with the potential to regulate carcinogenesis) for cancer prevention ( Saka-Herrán et al, 2022 ; Khazaaleh et al, 2022 ; Zhang et al, 2019 ; Longo et al, 2022 ; Cheung et al, 2023 ) ( Figure 1 ). Detailly, preclinical research revealed that statins might inhibit the cancer cell proliferation via countering the cell cycle at the G1-S phase and enhancing the cell apoptosis ( Ahmadi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous meta-analyses have suggested that statin use decreases the esophageal cancer 20 , stomach cancer risk 21 , colorectal cancer 22 , biliary trace cancer 23 , and prostate cancer 24 . On the contrary, significant associations of these cancers with the long-term use of anti-cholesterol drugs were not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Viability and apoptosis are on lipophilicity, in osteosarcoma [24], chondrosarcoma [41], or rhabdomyosarcoma [43], but no clinical data related to the differential effect of lipophilic vs hydrophilic statin in sarcomas were found. Data from other types of tumors show this action [80], being lipophilic statins more effective.…”
Section: Mechanisms Of Action Of Statins 41 Effects Derived From Lipo...mentioning
confidence: 96%